2017
DOI: 10.3941/jrcr.v11i7.2853
|View full text |Cite
|
Sign up to set email alerts
|

Mature cystic teratoma with high proportion of solid thyroid tissue: a controversial case with unusual imaging findings

Abstract: We describe a case of a mature cystic teratoma of the ovary with high proportion of solid thyroid tissue (< 50% of the entire tumor) in a childbearing woman. The patient presented with non-specific abdominal bloating. Pelvic ultrasound and magnetic resonance imaging revealed a complex cystic-solid tumor confined to the left ovary with an anterior fat-containing locus compatible with mature cystic teratoma and a posterior predominantly solid component with low signal intensity on T2-weighted images that was his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Low T1 and T2 signal shows simple cysts, whereas intermediate T1 and low T2 signal demonstrates colloid-filled follicles, resembling thyroid microscopic appearance [ 1 , 8 ]. Fat suppression techniques are used in MRI to evaluate the fat component of the tumor [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low T1 and T2 signal shows simple cysts, whereas intermediate T1 and low T2 signal demonstrates colloid-filled follicles, resembling thyroid microscopic appearance [ 1 , 8 ]. Fat suppression techniques are used in MRI to evaluate the fat component of the tumor [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant struma ovarii is a rare tumor which does not often metastasize. 1,3 Histological differentiation of benign from malignant struma ovarii has been proven both difficult and of limited clinical value. Previous reports have shown that a proportion of histologically benign tumors will behave in a malignant fashion and that the majority of malignant tumors will not progress after local resection.…”
Section: Resultsmentioning
confidence: 99%
“…A Case Report 1 Karim Jamal, 2 Mechteld C de Jong, 3 Ian Proctor, 4 Simon Morley, 5 Suganya Sivabalasingham, 6 Tarek E Abdel-Aziz, 7 liver lesions to be iodine-avid and therefore presumed metastasis.…”
Section: Management Of Metastatic Struma Ovarii With Papillary Thyroimentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of a squamous cell carcinoma arising in an ovarian MCT ranges from 9.7-15.6 cm (1, 4-8, 16, 17) and median age of patients is approximately 55 years (1,16), whereas the size of thyroid carcinoma in an MCT ranges from 5 to 20 cm and the median age of patients is about 42-45 years (12,15). The preoperative detection of malignant transformation is very difficult and the diagnostic accuracy of ultrasound, magnetic resonance imaging and computed tomography (CT) is uncertain (18)(19)(20)(21)(22)(23). Malignancy is usually diagnosed post-operatively based on histopathologic findings (6,8,13,15,24).…”
mentioning
confidence: 99%